Exhibiting atrocity : memorial museums and the politics of past violence - Sodaro, Amy, 1975- (New Brunswick : Rutgers University Press, 2018)
"Today, nearly any group or nation with violence in its past has constructed or is planning a memorial museum as a mechanism for confronting past trauma, often together with truth commissions, trials, and/or other symbolic or material reparations. Exhibiting Atrocity documents the emergence of the memorial museum as a new cultural form of commemoration, and analyzes its use in efforts to come to terms with past political violence and to promote democracy and human rights. Through a global comparative approach, Amy Sodaro uses in-depth case studies of five exemplary memorial museums that commemorate a range of violent pasts and allow for a chronological and global examination of the trend: the US Holocaust Memorial Museum in Washington, DC; the House of Terror in Budapest; the Kigali Genocide Memorial Centre in Rwanda; the Museum of Memory and Human Rights in Santiago, Chile; and the National September 11 Memorial Museum in New York. Together, these case studies illustrate the historical emergence and global spread of the memorial museum and show how this new cultural form of commemoration is intended to be used in contemporary societies around the world"--
Memorial museums: the emergence of a new form -- The US Holocaust Memorial Museum: the creation of a "living memorial" -- The House of Terror: "the only one of its kind" -- The Kigali Genocide Memorial Centre: building a "lasting peace" -- The Museum of Memory and Human Rights: "a living museum for Chile's memory" -- The National September 11 Memorial Museum: "to bear solemn witness" -- Memorial museums: promises and limits.
Includes bibliographical references (pages 195-204) and index.
Keywords: Memorialization -- Museums; Political atrocities -- Museums; Genocide -- Museums; Crimes against humanity -- Museums; Collective memory; Historical museums